Factors that Influence Frequency of ADHD Diagnosis - J Gordon Millichap (Pediatric Neurology Briefs, 2006)
Factors associated with the probability of attention-deficit/hyperactivity (ADHD) diagnosis among third grade US elementary school children were investigated in a nationally representative sample of 9278 children in the 2002 follow-up of the Early Childhood Longitudinal Survey Cohort conducted at University of Texas, Austin, TX.